FEATURES OF TRANSPORT OF CERTAIN ELEMENTS IN WATER NORTH CASPIAN - E. V. Chujko; O. V. Popova (Юг России: экология, развитие, 2014)
Major influence on the form of migration of trace elements in the North Caspian has Volga runoff. The bulk of the elements in the Volga waters carried in the suspended solids. The exception is zinc, transports mainly in dissolved form.In article presents the results of a study of dissolved and suspended forms of zinc, copper, lead, and manganese in the surface water of the North Caspian Sea from 2002 to 2009. On the basis of the received data the ratio of dissolved and suspended forms of trace elements studied. According to calculations, the bulk of the copper, lead and manganese is carried in the suspended solids. Zinc migrates mainly in dissolved form. The dominant form of migration of the metal increases, depending on the season. For zinc, the migrant in the ionic state, and for copper, lead, manganese, transferring primarily in suspension, in the autumn period the increase in the proportion of dissolved (Zn) and suspended forms (Cu, Pb, Mn), respectively. Increase in the proportion of ionic forms of metals in the North Caspian occurred episodically in local areas. Over the entire study period the greatest number of excess dissolved form of weighted metal observed in the central part of the shallow zone predustevogo space p. Volga near the exit of the Kirov and Belinsky channels.